Persepsi Generasi Milenial tentang Keamanan Kosmetik Bersertifikat Halal dan Keputusannya dalam Menggunakan Kosmetik Wardah - Abdul Rachman; Nur Jamaludin; Raihana Fairuza Amira (STES Islamic Village, 2022)
This study's objective is to investigate the factors of halal certification, such as comprehension, trust, and safety, and to determine the impact of each variable on purchasing decisions for halal cosmetics. This is a descriptive study in which understanding, trust, and safety are independent variables and purchasing decision is the dependent variable. This study employs a closed questionnaire for data collection, literature reviews, and other research-related references. This study's sample consisted of 103 Islamic Village College students selected using the method of purposive sampling with the inclusion of students who have ever purchased Wardah cosmetic products. The data are analyzed using the classic assumption test and statistical tests of multiple linear regression analysis (F test and T test) in SPSS 23. According to the study's findings, 1) comprension have a positive but insignificant effect on the buying decision of halal cosmetics, 2) trust have a positive and significant effect on the buying decision of halal cosmetics, 3) safety had a positive and significant effect on the buying decision, and 4) Halal certification have a positive and significant effect on the buying decision of halal cosmetics.